Analisis Kualitas Pelayanan Stasiun Kereta Api Berdasarkan Tingkat Kepuasan Pengguna Layanan (Studi Kasus: Stasiun Tanjung Karang) - Mentiring, Benny; Oktarina, Devi; Dirangga, Karlia (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2023)
The service quality of Tanjung Karang Station is said to be good if service users are satisfied with the services obtained as expected. This study aims to identify the level of satisfaction of service users at the Tanjung Karang Railway Station. Data collection was carried out by distributing questionnaires to 100 respondents. The questionnaire was prepared according to the guidelines of the Minister of Transportation Regulation concerning SPM no.48 of 2015. To measure the level of satisfaction of service users on various factors related to Tanjung Karang station services, the Im-portance Performance Analysis (IPA) method was used. Based on the results of the questionnaire analysis using the IPA method, it was concluded that the highest quality of service was the factor (facilities) question variable P6, overall the facilities provided by the train were adequate (com-plete and functioning properly), namely 121.50% of this question variable was considered very satisfactory because it has exceeded the percentage > 100%. While the lowest service quality is the factor (Security) question variable P14 lighting in the station 83,97% of this question variable is considered to have met the level of satisfaction because it has exceeded the percentage of 80-100%. The average value of service user satisfaction at the Tanjung Karang station is 96,81%, from this value the service quality of the Tanjung Karang station is considered satisfactory. With a satisfactory service quality value, service quality greatly influences service user satisfaction at the Tanjung Karang Railway Station. Key words: Tanjung Karang Railway Stations, Minimum Service Standards, Importance Performance Analysis (IPA), Satisfaction of Service Users.